Winning the team event at major international archery competitions - Jacobs, D. B.; Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2017)
Major international target archery competitions usually include a 72-arrow ranking round, followed by one-on-one knockout matches conducted with a small number of arrows until one team remains. This article considers the relation between a team`s placement from the ranking round and the likelihood of that team finishing in a top spot following the one-on-one knockout matches. The team`s ranking round score has been used for two purposes: to indicate the ability of each archer in the matches and to calculate the probability of the team winning sufficient matches in succession to succeed in the competition. The finding of the study is that the probability of the team winning the competition decreases exponentially with ranking place. This finding adequately reflects the results from all major international target archery competitions held between 2000 and 2015 inclusive. Due to the importance of the ranking round, a team needs to finish in or near the top 4 places in the ranking round for the team to have a chance at medalling. The score trend for fourth place provides an indication of the likely scores required to medal in future competitions, such as the 2020 Olympic Games.